Incidence and risk factors of postoperative acute pancreatitis after pancreaticoduodenectomy: a systematic review and meta-analysis - Wu, Zhouyu; Zong, Kezhen; Zhou, Baoyong; Yin, Kunli; Zhang, Anlan; Li, Ming (Frontiers in Surgery, 2023)
Background: Postoperative acute pancreatitis (POAP) is a specific complication after pancreatectomy. The acute inflammatory response of the residual pancreas may affect the healing of pancreatoenteric anastomoses, leading to postoperative pancreatic fistulas (POPFs), abdominal infections, and even progressive systemic reactions, conditions that negatively affect patient’s prognoses or can even cause death. However, to the best of our knowledge, no systematic reviews or meta-analytic studies have assessed the incidence and risk factors of POAP after pancreaticoduodenectomy (PD). Method: We searched PubMed, Web of Science, Embase, and Cochrane Library databases for relevant literature describing the outcomes of POAP after PD until November 25, 2022, and we used the Newcastle–Ottawa Scale to assess the quality of the studies. Next, we pooled the incidence of POAP and the odds ratios (ORs) and 95% confidence intervals (CIs) of the risk factors using a random-effect meta-analysis. I2 tests were used to assess heterogeneity between the studies. Results: We analyzed data from 7164 patients after PD from 23 articles meeting our criteria. The results of the meta-analysis showed a 33% (95% CI, 32–34) incidence of POAP after PD. Subgroup analyses on the basis of different POAP diagnostic criteria showed POAP incidences at 15% (95% CI, 5–38) in the International Study Group for Pancreatic Surgery (ISGPS) group, 51% (95% CI, 42–60) in the Connor group, 7% (95% CI, 2–24) in the Atlanta group, and 5% (95% CI, 2–14) in the unclear group. Being a woman [OR (1.37, 95% CI, 1.06–1.77)] or presenting a soft pancreatic texture [OR (2.56, 95% CI, 1.70–3.86)] were risk factors for POAP after PD. Conclusion: Our results show that POAP was common after PD surgery and that the incidence of POAP varies widely according to different definitions. Large-scale reports are still needed and surgeons should remain aware of this complication.